Ectomycorrhizas with P axillus involutus enhance cadmium uptake and tolerance in P opulus × canescens - Ma, Yonglu; He, Jiali; Ma, Chaofeng; Luo, Jie; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi‐Bin (Plant, Cell & Environment, 2014)
Ectomycorrhizas ( EMs ), which are symbiotic organs formed between tree roots and certain fungi, can mediate cadmium ( Cd ) tolerance of host plants, but the underlying physiological and molecular mechanisms are not fully understood. P opulus × canescens was inoculated with or without P axillus involutus (strain MAJ ) and subsequently exposed to 0 or 50 μM CdSO 4 . Higher net Cd 2+ influx in EMs well corresponded to higher transcript levels of genes involved in Cd 2+ uptake, transport and detoxification processes than those in nonmycorrhizal roots. Higher CO 2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to nonmycorrhizal poplars despite higher Cd 2+ accumulation. , Abstract Ectomycorrhizas ( EMs ), which are symbiotic organs formed between tree roots and certain fungi, can mediate cadmium ( Cd ) tolerance of host plants, but the underlying physiological and molecular mechanisms are not fully understood. To investigate EMs mediated Cd tolerance in woody plants, P opulus × canescens was inoculated with P axillus involutus (strain MAJ ) to establish mycorrhizal roots. Mycorrhizal poplars and non‐mycorrhizal controls were exposed to 0 or 50 μ M CdSO 4 . EMs displayed higher net Cd 2+ influx than non‐mycorrhizal roots. Net Cd 2+ influx was coupled with net H + efflux and inactivation of plasma membrane ( PM ) H + ‐ ATPases reduced Cd 2+ uptake of EMs less than of non‐mycorrhizal roots. Consistent with higher Cd 2+ uptake in EMs , in most cases, transcript levels of genes involved in Cd 2+ uptake, transport and detoxification processes were increased in EMs compared to non‐mycorrhizal roots. Higher CO 2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to non‐mycorrhizal poplars despite higher Cd 2+ accumulation. These results indicate that mycorrhizas increase Cd 2+ uptake, probably by an enlarged root volume and overexpression of genes involved in Cd 2+ uptake and transport, and concurrently enhance P o. × canescens Cd tolerance by increased detoxification, improved nutrient and carbohydrate status and defence preparedness.